2018
DOI: 10.1115/1.4039642
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Natural Convection Around a Circular Cylinder With Different Geometries of Cylinders Inside a Square Enclosure Filled With Ag-Nanofluid Superposed Porous-Nanofluid Layers

Abstract: Numerical simulations are carried out for fluid flow and natural convection heat transfer induced by a temperature difference between a hot inner cylinder with different geometries (i.e., circular; triangular; elliptic; rectangular; and rhombic) and a cold outer square enclosure filled with nanofluid superposed porous-nanofluid layers. The Darcy–Brinkman model is applied for the saturated porous layer with nanofluid. Moreover, the transport equations (mass, momentum, and energy) are solved numerically using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…This method has been simplified for coupling of the momentum equation between nano-fluid domain and porous domain. The governing equations for the nano-fluid domain in the dimensional form are [54,61] The physical characteristics of the nanofluid could be expressed as follows:…”
Section: Figure 1 Schematic Diagram Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…This method has been simplified for coupling of the momentum equation between nano-fluid domain and porous domain. The governing equations for the nano-fluid domain in the dimensional form are [54,61] The physical characteristics of the nanofluid could be expressed as follows:…”
Section: Figure 1 Schematic Diagram Of the Problemmentioning
confidence: 99%
“…They have concluded that average Nusselt number decreases with the increase of the Reynolds number and corrugations number. Recently, Hussain and Rahomey [54] studied the natural convection between various internal cylinder bodies like circular, square, triangular and elliptical placed within a square enclosure filling by nanofluid and porous media saturated by the same nano-fluid. Results have shown that is better in heat transfer rate.…”
Section: Introductionmentioning
confidence: 99%
“…In all cases, an increment in Rayleigh and Darcy numbers expand the heat transfer and average Nusselt number. Also, Hussain and Rahomey [10] has been showed the efficiency of difference geometries inside a square porous cavity. The effect of magnetohydrodynamic natural convection in a nanofluid-porous annulus area has been studied by Sheikholeslami and Shehzad [11], Sheikholeslami et al, [12] and Ahmed et al, [13].…”
Section: Introductionmentioning
confidence: 99%
“…We can cite a review of Khanafer et al, [1] and Kasaeian et al, [2]. Many theoretical and experimental investigations have been realized in this domain, we quote about that Sheikhzadeh and Nazari [4] have studied the steady state natural convection in porous medium saturated with (Al2O3-Water) inside differentially heated square cavity [3][4][5][6][7][8][9][10][11][12][13][14][15]. The governing equations have solved by finite volume approach using SIMPLER algorithm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation